Thirty-year patency of a coronary sequential venous bypass graft - Molardi, Alberto; Nicolini, Francesco; Benassi, Filippo; Gallingani, Alan; Gherli, Tiziano; Spaggiari, Igino (Acta Biomedica Atenei Parmensis, 2014)
The optimal conduit of second choice in surgical coronary revascularization remains a matter of debate. Radial artery grafts are believed to have a better patency rate than the saphenous vein grafts, although no conclusive results have been reported. This report describes the late result of a coronary revascularization with sequential venous bypass performed 30 years earlier. Methods An 80-year-old woman was admitted for dyspnoea on exertion and recent-onset angina due to severe aortic valve stenosis. Thirty years earlier, the patient had undergone revascularization with coronary bypass grafting performed using a sequential saphenous vein graft anastomosed on first diagonal branch and on left anterior descending coronary artery. Coronary angiography showed the occlusion of the native left anterior descending artery and the good patency of the previous described sequential vein graft. Results Surgical inspection confirmed the patency and the soft pliability of the venous graft and the surgeon decided to do not replace the previous graft with a pedicled LIMA (Left Internal Mammary Artery) graft. The patient underwent 21-mm biological Edwards Perimount Magna Ease prosthesis implantation. Postoperative course was uneventful and the patient was discharged on the seventh day after surgery. Conclusions This case report demonstrated the potential extreme long-term patency of a sequential saphenous vein graft in coronary bypass surgery, raising the question if vein grafts should be really considered the conduits of last resort for coronary artery bypass surgery. Long-term follow-up of randomized trials comparing radial artery versus saphenous vein grafts are warranted in order to give conclusive answers to this ongoing debate.